2018
DOI: 10.1016/j.yjmcc.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage oligomeric matrix protein is a novel notch ligand driving embryonic stem cell differentiation towards the smooth muscle lineage

Abstract: Cartilage oligomeric matrix protein (COMP), a protective component of vascular extracellular matrix (ECM), maintains the homeostasis of mature vascular smooth muscle cells (VSMCs). However, whether COMP modulates the differentiation of stem cells towards the smooth muscle lineage is still elusive. Firstly, purified mouse COMP directly induced mouse embryonic stem cell (ESC) differentiation into VSMCs both in vitro and in vivo, while the silencing of endogenous COMP markedly inhibited ESC-VSMC differentiation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The cDNA encoding the mouse AT1a (NCBI Reference sequence: NM_177322.3) receptor was subcloned in-frame into the Flag vector to generate the indicated plasmids. For the co-IP assay, COS-7 cells were transfected with these plasmids and then incubated with the purified COMP protein 75 for 30 min. The cell lysates were incubated with an anti-Flag antibody or control IgG followed by Protein A/G agarose beads, and COMP protein expression was examined using western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The cDNA encoding the mouse AT1a (NCBI Reference sequence: NM_177322.3) receptor was subcloned in-frame into the Flag vector to generate the indicated plasmids. For the co-IP assay, COS-7 cells were transfected with these plasmids and then incubated with the purified COMP protein 75 for 30 min. The cell lysates were incubated with an anti-Flag antibody or control IgG followed by Protein A/G agarose beads, and COMP protein expression was examined using western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…To screen for the possible functions of the peptides, we selected a single concentration of 100 nM for most of the assays. We based our choice on the maximum amount of peptides that 10 μg/mL of the parent protein COMP would release if COMP was completely cleaved, as COMP demonstrates bioactive effects in vitro at this concentration 17 , 18 and COMP is present in this concentration range in human serum. 19 …”
Section: Methodsmentioning
confidence: 99%
“…Notch3 was also required to maintain the smooth muscle gene expression profile and the morphological characteristics of the pulmonary artery after birth [72] . Our lab recently found that cartilage oligomeric matrix protein interacts with the activated Notch1 signaling pathway to drive ESC differentiation into VSMCs [73] …”
Section: Major Signaling Pathways Involved In Vsmc Developmentmentioning
confidence: 99%
“…[72] Our lab recently found that cartilage oligomeric matrix protein interacts with the activated Notch1 signaling pathway to drive ESC differentiation into VSMCs. [73] Notch signaling is crucial for the NC precursors to differentiate into proper OFT patterns and in aortic arch artery formation. Suppressing Notch activity in these cells in mice causes malformation of the smooth muscle layer of the aortic arteries, resulting in congenital heart defects, namely, pulmonary artery stenosis and aortic arch patterning defects.…”
Section: Notch Signalingmentioning
confidence: 99%